Hypervalent iodine(III)-mediated decarboxylative acetoxylation at tertiary and benzylic carbon centers - Kiyokawa, Kensuke; Okumatsu, Daichi; Minakata, Satoshi (Beilstein Journal of Organic Chemistry, 2018)
The decarboxylative acetoxylation of carboxylic acids using a combination of PhI(OAc)2 and I2 in a CH2Cl2/AcOH mixed solvent is reported. The reaction was successfully applied to two types of carboxylic acids containing an α-quaternary and a benzylic carbon center under mild reaction conditions. The resulting acetates were readily converted into the corresponding alcohols by hydrolysis.
Keywords: acetoxylation; carboxylic acids; decarboxylation; hypervalent iodine; iodine